Decision-making and future planning for children with life-limiting conditions: a qualitative systematic review and thematic synthesis - Popejoy, Emma; Pollock, Kristian; Almack, Kathryn; Manning, Joseph C.; Johnston, B. (Wiley, 2017)
Background